QOL-15. VALIDITY AND RELIABILITY EVALUATION OF PRO-CTCAETM FOR ADULT DIFFUSE GLIOMAS PATIENT IN CHINESE POPULATION. (VERONICA): A PRELIMINARY DELPHI STUDY. (14th November 2022) - Luo, Chen; Wu, Shuai; Cai, Linbo; Chen, Juxiang; Chen, Song; Fei, Zhou; Kong, Lin; Li, Sanzhong; Ma, Hui; Mou, Yonggao; Qiu, Xiaoguang; Shu, Kai; et al.
Abstract: OBJECTIVES: Given the increasing importance of patient's perspective in adverse events reporting, Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE™) has been proposed as new PRO measures in oncology; however, its implementation has not yet been evaluated in glioma patients, and standardized selection process of priority symptom terms has not been applied. METHODS: A total of 16 experts (13 neurosurgeons, 2 radiotherapists, 1 psychiatrist) from 14 medical centers in China were invited to participate in a consensus-seeking 2-round online Delphi survey. Participants rated the level of their agreement with each symptom term likely to occur during adult diffuse gliomas treatment on a 5-point Likert scale. Terms not reaching consensus over the first round were modified in the second rounds. Consensus was defined as content validity index (CVI) > 0.78，coefficient of variation (CV)< 0.35 and average Likert score > 3.00. RESULTS: Experts reached a consensus on 21 PRO-CTCAE™ symptom terms in the first Delphi round, and 10 terms in the second round. Likert scale scoring among all experts showed significant consistency (Round 1: Kendall's W= 0.415，p＜0.001; Round 2: Kendall's W = 0.351，P＜0.001). The 31 terms (38.75%) screened out of all 78 terms covered neurological symptoms(n=7), psychiatric symptoms(n=6), dermatological symptoms(n=6), gastrointestinal symptoms(n=5) and other common postoperative systemic symptoms of glioma patients. CONCLUSIONS: We identified a customized PRO-CTCAE™ questionnaire containing a core set of priority symptom terms for the adult diffuse glioma through a 2-round Delphi survey. Next, a prospective, multi-center, real-word study would be performed to assess the validity, reliability and responsiveness of the customized PRO-CTCAE™ for adult diffuse glioma patients in Chinese population (VERONICA).